Porcine Anti-viral Immunity: How Important Is It? - Lager, Kelly M.; Buckley, Alexandra C. (Frontiers in Immunology, 2019)
Pork has become the number one meat consumed worldwide. Meeting the demand for pork has forced the revolution of swine production from traditional husbandry practices that involved a few pigs or small herds to intensive concentration of swine raised in multisite production systems. This dramatic change has made the production of pork very efficient, but it has also changed the ecology of many swine diseases, may encourage the emergence of new diseases, and amplifies the economic impact of swine diseases. Sustained treatment of diseases in livestock production is not feasible making prevention of disease a priority. Prevention of livestock diseases involves eliminating exposure to pathogens and anti-viral strategies to prevent or reduce clinical disease. For some swine diseases, efficacious vaccines can be made, however, for other diseases the host/pathogen relationship is more complex and efficacious vaccines are not available. Given the increasing demand for pork, the development of new approaches to improve swine anti-viral immunity is critical. Rate-limiting steps to improving vaccines are understanding how the pathogen interacts with the host’s immune system, any immunopathology resulting from such interactions and how the host’s immune system resolves the infection. Solving this puzzle will require sustained research and may require new technologies to battle contemporary diseases now wreaking havoc in swine production systems around the world. This Special Issue will focus on current swine viral diseases that are the most challenging to the global production of pork with contributions focusing on anti-viral immunity.